The Silk Road and Afghanistan: A Nexus of Trade, Culture, and Geopolitical Exchange - Mastali Niazai; Fayaz Gul Mazloum Yar (Green Publisher Indonesia, 2025)
This article examines Afghanistan's role in the Silk Road and its impact on the country's historical, cultural, economic, and geographical transformations. Due to its strategic geographical position in the heart of Asia, Afghanistan has historically served as a bridge connecting various civilizations of the East and West. This role has allowed Afghanistan to experience extensive commercial and cultural influences from the Silk Road. This review article analyzes the historical, cultural, and economic impacts of the Silk Road on Afghanistan and assesses the country’s role as a strategic hub in trade and cultural exchanges between Asia and Europe. This study employs a narrative review approach, conducting a qualitative analysis of previous research by compiling and examining information from various historical, geographical, and cultural sources. The key findings of this study indicate that Afghanistan played a fundamental role as a bridge for commercial and cultural exchanges between the East and West along the Silk Road. Its geographical location positioned it along major trade routes, including those involving silk, spices, and metals. Furthermore, the cultural and religious exchanges, including the introduction of various religions and artistic and linguistic influences, have been significant throughout Afghanistan’s history. Cities such as Balkh, Herat, Kandahar, and Kabul were recognized as major trade and cultural centers along this route. The findings of this research highlight that Afghanistan, due to its strategic position along the Silk Road, played an unparalleled role in facilitating cultural and commercial development among civilizations.